Stomach cancer disparity among Korean Americans by tumor characteristics: comparison with non-Hispanic whites, Japanese Americans, South Koreans, and Japanese. - Lee, Eunjung (Cancer Epidemiol Biomarkers Prev, 2016)
BACKGROUND: Stomach cancer incidence shows substantial racial-ethnic disparity in the United States (US), with Korean Americans experiencing by far the highest incidence. We examined stomach cancer incidence trends in Korean Americans by tumor subsite, histology and stage, and compared them with incidence rates in racial-ethnic groups with the second highest rate (Japanese Americans) and the lowest rate (non-Hispanic whites; NHWs) as well as populations in South Korea and Japan. METHODS: We calculated age-adjusted incidence rates by racial-ethnic groups and sex, by tumor characteristics, using the 1988–2012 California Cancer Registry data. Data on South Korea and Japan were obtained from the literature and other resources. RESULTS: Between 1988 and 2012 in California, Korean Americans had about 5 times greater incidence than NHWs and twice that of Japanese Americans. Tumor characteristics differed by ethnic group and gender. The incidence in Korean Americans has declined during recent years, for both cardia- and non-cardia sites and for both intestinal- and diffuse-type histology. Although Korean Americans were diagnosed at an earlier stage than other Californians, the proportion with localized disease (43%) was much smaller than in South Korea (57%), where population-based screening is available. CONCLUSIONS: Stomach cancer incidence declined in the highest risk ethnic groups. However, the persistent disparity between Korean Americans and other racial/ethnic groups warrants additional strategies for prevention and earlier diagnosis. IMPACT: Analysis of California Cancer Registry data identified a racial-ethnic subgroup with stomach cancer disparity who may benefit from targeted prevention and screening efforts.